2017
DOI: 10.1590/0001-3765201720160659
|View full text |Cite
|
Sign up to set email alerts
|

High consumption of sucrose induces DNA damage in male Wistar rats

Abstract: The purpose of this study was to determine the effects of the high consumption of sucrose on the levels of DNA damage in blood, hippocampus and bone marrow of rats. Male Wistar rats were treated for 4 months with sucrose (10% for 60 initial days and 34% for the following 60 days) in drinking water, and then, glycemia and glycated hemoglobin (A1C) were measured. Levels of DNA damage in blood and hippocampus were evaluated by the comet assay. The micronucleus test was used to evaluate chromosomal damages in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The obtained results evidenced an increase in LC3-II levels following the administration of trehalose and raffinose as compared with all the other treatments. Both trehalose and raffinose did not show any cytotoxic effect, as demonstrated by others [42,43]. Among these, trehalose induced an increase of expression of other autophagy markers, i.e., Beclin1 and ATG5, as already documented [40].…”
Section: Discussionsupporting
confidence: 77%
“…The obtained results evidenced an increase in LC3-II levels following the administration of trehalose and raffinose as compared with all the other treatments. Both trehalose and raffinose did not show any cytotoxic effect, as demonstrated by others [42,43]. Among these, trehalose induced an increase of expression of other autophagy markers, i.e., Beclin1 and ATG5, as already documented [40].…”
Section: Discussionsupporting
confidence: 77%
“…In brain cells, there is an association between high consumption of sucrose (a disaccharide formed by glucose and fructose) and increased levels of DNA damage, suggesting that DNA glycation reactions by fructose may be responsible for the damage found in brain cells in the present work. 52 Corroborating this, Yamazaki et al 53 found that excessive maternal fructose consumption impairs hippocampal function in offspring via epigenetic modification in brain-derived neurotrophic factor (BDNF) gene expression. 53 The hippocampus was the most affected area with reduced antioxidant activity and sulfhydryl content, leading to increased oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Early efforts to understand the effects of carbohydrate metabolism and DNA damage were made using Saccharomyces cerevisiae as a model and a systems biology approach (Barea and Bonatto 2008), showing that reactive carbonyl species (RCS) provided by sugar metabolism could be linked to DNA damage. The manuscript of Franke et al (2017) also addresses this question, and shows that the consumption of a high sucrose diet in rat model promotes DNA damage in hippocampus hence it contributes to the development of diabetes-associated neuropathologies. …”
mentioning
confidence: 99%